Community-Based Training on Burning and Wall Paint Finishing Techniques to Enhance Antique Wood Effects among Local Craft Practitioners - Defrata Harjuna Putra; Yuniana Cahyaningrum (Jurnal Abdimas Cendekiawan Indonesia, 2026)
Strengthening innovation within local craft communities requires mentoring approaches that encourage experimentation using accessible materials. This community-based training program was conducted in collaboration with Barata Sena Woodcraft, a small-scale enterprise in Surakarta employing eight local craftsmen. The activity aimed to introduce burning and wall-painting techniques as an alternative approach to enhancing the visual effects of antiques on wooden products. The program adopted a participatory model consisting of needs identification, technical demonstrations, guided practice, and reflective discussions. Participants were directly involved in wood preparation, controlled burning, and the application of layered wall paint to explore variations in texture and color intensity. Observational records and participant reflections indicate that 6 of 8 craftsmen (75%) perceived the technique as easy to integrate into their daily workflow. In contrast, seven participants (87.5%) reported increased confidence in experimenting with alternative finishing materials. The training also encouraged collaborative learning and creative exploration, contributing to product diversification and improved aesthetic value. These findings suggest that contextualized mentoring activities can support community empowerment by bridging traditional craftsmanship with adaptive finishing practices that remain feasible within small-scale production settings.